2016
DOI: 10.1093/conphys/cov060
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific individual variation of temperature tolerance associated with oxygen demand in the European sea bass (Dicentrarchus labrax)

Abstract: Here we explored the hypothesis that individual variation in thermal tolerance in the European sea bass is associated with other key performance traits involved in determining individual Darwinian fitness. Our finding that whole animal temperature tolerance positively correlates with cardiac size could suggest selection on the cardiorespiratory system may benefit thermal tolerance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 50 publications
0
20
0
Order By: Relevance
“…In the open ocean, fish often experience cold, hypoxic conditions during oscillatory dives which approach or extend beyond the depths at which the mixed layer ends and the oxygen minimum zone begins (Bernal et al., ). Segregation of vertical habitat use of open ocean fishes is driven by the physiological ability of species to maintain sufficient cardiorespiratory capacity for active behaviours under these challenging conditions (Bernal et al., , ), a trait governed by a suite of physiological factors which are known to show interindividual variation (Joyce et al., ; Ollivier, Marchant, Le Bayon, Servili, & Claireaux, ; Ozolina, Shiels, Ollivier, & Claireaux, ). This variation may ultimately manifest as differences in the maximum depth attainable by individual fish, or the amount of time fish spend at a given depth, and so give rise to intraspecific differences in vertical habitat use (Cosgrove, Arregui, Arrizabalaga, Goni, & Sheridan, ; Quayle, Righton, Hetherington, & Pickett, ; Vaudo et al., ), with implications for whether individuals are available to gears deployed at specific depths (Olsen, Heupel, Simpfendorfer, & Moland, ).…”
Section: The Capture Process and Selection On Physiological Traitsmentioning
confidence: 99%
“…In the open ocean, fish often experience cold, hypoxic conditions during oscillatory dives which approach or extend beyond the depths at which the mixed layer ends and the oxygen minimum zone begins (Bernal et al., ). Segregation of vertical habitat use of open ocean fishes is driven by the physiological ability of species to maintain sufficient cardiorespiratory capacity for active behaviours under these challenging conditions (Bernal et al., , ), a trait governed by a suite of physiological factors which are known to show interindividual variation (Joyce et al., ; Ollivier, Marchant, Le Bayon, Servili, & Claireaux, ; Ozolina, Shiels, Ollivier, & Claireaux, ). This variation may ultimately manifest as differences in the maximum depth attainable by individual fish, or the amount of time fish spend at a given depth, and so give rise to intraspecific differences in vertical habitat use (Cosgrove, Arregui, Arrizabalaga, Goni, & Sheridan, ; Quayle, Righton, Hetherington, & Pickett, ; Vaudo et al., ), with implications for whether individuals are available to gears deployed at specific depths (Olsen, Heupel, Simpfendorfer, & Moland, ).…”
Section: The Capture Process and Selection On Physiological Traitsmentioning
confidence: 99%
“…However, adjustments at any of these stages may result in physiological, functional and/or fitness-related trade-offs. For example, sea bass (Dicentrarchus labrax) that had higher temperature tolerance had better cardiac function and lower SMR, but also had reduced critical swimming speed compared with those with lower temperature tolerance (Ozolina et al, 2016).…”
Section: Metabolic Variables Are Affected By Exposure Timementioning
confidence: 99%
“…Atlantic salmon, [ 10 ]). We have shown separately [ 21 ] that robust performance under one environmental challenge test does not necessarily correlate with success in another (thermal tolerance and swimming capacity; and also see [ 9 ]). Moreover, there was no correlation between HCT performance and swimming performance in a preliminary study conducted on this cohort of sea bass (data not shown).…”
Section: Discussionmentioning
confidence: 99%